An exploratory study of accounting and reporting practice for waqf among state Islamic religious councils in Malaysia - Abu Talib, Nori Yani; Abdul Latiff, Radziah; Aman, Aini; Palil, Mohd Rizal (Universiti Kebangsaan Malaysia, 2018)
Nowadays, Muslims has been exposed to the increasing number of waqf practice and the importance of waqf to the society due to the huge benefits in the socio-economic development and assist the poor and those in need. However, there is a lack of accounting system and systematic management of waqf assets and the absence of written procedures of recording financial transactions of waqf assets. The purpose of this research is to identify the range of differences of waqf accounting practice in details and discover the rationale behind the diverse of accounting and reporting practices for waqf. It examines accounting and reporting practices in terms of recognition, measurement and disclosure in eleven selected state waqf institutions. It provides an insightful meaning of the issues and challenges on how accounting is practice in these State Islamic Religious Councils (SIRCs). From the analysis conducted, it is found that the financial accounting and reporting related to waqf in SIRCs differs in terms of the guideline used, the recognition and measurement (valuation of waqf asset) as well as the disclosure and reporting practice of waqf. The variations of accounting and reporting practices in these waqf institutions portray the dynamism of waqf accounting and reporting among SIRCs in Malaysia. The reason for the variation in accounting practice is attributed to the nature of SIRCs governance where each SIRC is headed by its ruler (Sultan) as the ultimate authority in Islam and the fatwa councils’ decision. The decision of the Board members with regard to the management and administration of waqf may differ in each states.